Fire behaviour of tabique wall – experimental and numerical study - Ferreira, Débora (2016)
This paper present a study on the behaviour of tabique walls, conceming its tire resistance. This work is based on the experimental analysis of real scale tabique paneis. Such paneis were made in pine wood with an earth-based mortar finishing. In arder to assess the earthbased mortar thickness effect on the fíre resistance of the wall, three specimens were tested with different mortar thickaesses of 15 mm, 10 mm and 5 mm. The experimental models were tested in a fíre-resistance íümace according to the ISO 834 standard fíre curve. A numerical model was developed in order to assess the tabique wall behaviour under fíre conditions and was validated with experimental results.